The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su13116082
|View full text |Cite
|
Sign up to set email alerts
|

Improving Energy Efficiency of Barley Production Using Joint Data Envelopment Analysis (DEA) and Life Cycle Assessment (LCA): Evaluation of Greenhouse Gas Emissions and Optimization Approach

Abstract: Eco-efficiency has become a cornerstone in improving the environmental and economic performance of farms. The joint use of life cycle assessment (LCA) and data envelopment analysis (DEA), known as LCA + DEA methodology, is an expanding area of research in this quest. LCA estimates the environmental impacts of the products or services, while DEA evaluates their efficiency, providing targets and benchmarks for the inefficient ones. Because energy consumption and environmental quality are highly interdependent, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 57 publications
(75 reference statements)
2
9
0
Order By: Relevance
“…On the other hand, fuel and pesticides are also manageable inputs, such that decreasing the consumed energy in these two inputs can improve the efficiency of the production of irrigated wheat and -in other wordsthe production of more crops by the consumption of each unit of energy. Findings for barley revealed that reduction in the consumption of diesel fuel and chemical fertilizers (such as nitrogen phosphorous) offered the greatest possibilities for energy saving [23] which are compatible with the findings of this research. Biomass can be considered as a source for improving soil nutrient and, thus, reducing fertilizers application, because of lower price, renewable and no secondary pollution [24,25].…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, fuel and pesticides are also manageable inputs, such that decreasing the consumed energy in these two inputs can improve the efficiency of the production of irrigated wheat and -in other wordsthe production of more crops by the consumption of each unit of energy. Findings for barley revealed that reduction in the consumption of diesel fuel and chemical fertilizers (such as nitrogen phosphorous) offered the greatest possibilities for energy saving [23] which are compatible with the findings of this research. Biomass can be considered as a source for improving soil nutrient and, thus, reducing fertilizers application, because of lower price, renewable and no secondary pollution [24,25].…”
Section: Resultssupporting
confidence: 88%
“…The results confirm that an optimization of resource use must be planned for the wheat production units in Iran if the environmental footprint has to be truncated. This has also been advocated strongly by other researches who have applied the LCA + DEA method to agricultural production systems [59][60][61]. In other words, the crux of the LCA + DEA method is the eco-efficiency concept-Units operating inefficiently must learn from the best practices of the efficient units in the region and adopt those in order to reduce their adverse environmental impacts.…”
Section: Dea Performancementioning
confidence: 99%
“…juice (Khanali et al., 2020), greenhouse strawberry ( Fragaria sp.) (Hosseini‐Fashami et al., 2019), and barley ( Hordeum vulgare L.) (Payandeh et al., 2021), durum wheat ( Triticum durum Desf.) (Failla et al., 2020), and oil bearing crops (Restuccia et al., 2013).…”
Section: Introductionmentioning
confidence: 99%